Awareness of Hand Hygiene among Dentists- A Questionnaire Survey - Deepika. R1, Anitha Roy2 , A.K. Anjali3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Dentistry is a service sector where the doctors are in close contact with the patients. Hand hygiene is veryimportant in the dental practice as it can prevent infection to a great extent. The aim of the survey was toassess the importance of hand hygiene among dentists. A Questionnaire of 15 questions was prepared andcirculated in the google forms, the responses were collected, compiled, and updated on the SPSS softwarefor data analysis. Pie charts and bar graphs were used to evaluate and interpret the results. Chi-Squaretest was carried out to check statistical significance and p value <0.05 was considered as significant. Theresults obtained from the dentists who participated in the survey provide that the dentists were aware ofhand hygiene protocol and the survey showed that hand hygiene is important to every dentist in their dentalpractice . 98.1% of the population agreed that maintenance of hand hygiene by the dentists prevents thespread of infections; 81.1% of the dentists participated were aware that 7 steps involved in the hand hygieneprotocol ; 85% of the dentists were aware that, a minimum of 20 seconds are required for proper handwashingto maintain the hand hygiene, All the dentists participated in this survey agreed that hand hygiene has tobe maintained definitely before the patient contact; 97.2% of dentists also suggested that hand hygienemaintenance is more necessary among the health care workers and 74.8% of the dentists agreed as handhygiene is the most important criterion among their dental clinics. Thus, This survey could make awarenessamong the dentist regarding hand hygiene protocol.